The Impact of Debate Lessons, Powered by Generative AI, on Student Learning - Seow Yongzhi (IAFOR Journal of Education)
Humanities education in Singapore at the secondary level emphasises the inquiry-based learning pedagogical approach to engage students, inculcate critical thinking skills, and achieve the necessary knowledge and skills outcomes stipulated by the national curriculum. Inquiry-based learning is structured by a Humanities inquiry cycle involving four steps and can take various forms in the classroom. In this paper, I explore the use of debate as an active learning tool to enact inquiry lessons in Social Studies, framed by the inquiry cycle and leveraging Generative AI tools. I ran 5 debates for two Grade 9 classes comprising 79 students over two schooling terms (20 teaching weeks). Student speakers were assigned for each debate, and all students formed teams to do research with the help of AI tools such as Chat GPT and Microsoft CoPilot. Through student preparatory work, student survey data, and teacher observations, I find that debates are powerful devices to build excitement and spark joy amongst students but require a high degree of preparatory work and active student management by the teacher to achieve desired knowledge outcomes. As a teaching tool, debates can deepen reflection and foster critical thinking on specific topics, and debate lessons foster a positive learning environment that celebrate learning and improve student outcomes.